Influence of maternal nutrition and one-carbon metabolites supplementation on bovine antimicrobial peptides in fetal and maternal tissues - Daneshi, Mojtaba; Borowicz, Pawel P.; Hirchert, Mara R.; Entzie, Yssi L.; Syring, Jessica G.; King, Layla E.; Safain, Kazi Sarjana; Anas, Muhammad; Reynolds, Lawrence P.; Ward, Alison K.; Dahlen, Carl R.; Crouse, Matthew S.; et al. (Frontiers in Veterinary Science, 2024)
IntroductionMaternal nutrition during pregnancy critically influences offspring development and immune function. One-carbon metabolites (OCM) are epigenetic modifiers that may modulate antimicrobial peptide (AMP) expression, which is vital for innate immunity. This study investigated the effects of maternal nutrient restriction and OCM supplementation on mRNA expression of AMP in fetal and maternal lung, mammary gland, and small intestine of beef cattle.MethodsTwenty-nine crossbred Angus beef heifers were synchronized for estrus and artificially inseminated. They were assigned to one of four treatments in a 2 × 2 factorial design: nutritional plane [control (CON) vs. restricted (RES)] and OCM supplementation [without OCM (−OCM) or with OCM (+OCM)]. Heifers on the CON diet were fed to gain 0.45 kg/day, while RES heifers were fed to lose 0.23 kg/day. Treatments were applied from day 0 to 63 of gestation, after which all heifers were fed a common diet to gain 0.45 kg/day until day 161 of gestation, when samples were collected. Quantitative RT-qPCR was used to assess mRNA expression of AMP.ResultsNutritional plane had no effect (p ≥ 0.24) on mRNA expression of AMP in either the fetus or dams. However, the mRNA expression of cathelicidin5 (CATHL5; p = 0.07) and bovine neutrophil β-defensin5 (BNBD5; p = 0.07) in the fetal lung and mammary gland, respectively, was lower in the +OCM groups compared to the −OCM groups. In the maternal small intestine, the expression of enteric β-defensin (EBD) was lower (p = 0.01) in the +OCM groups compared to the −OCM groups. Additionally, in the maternal lung, there was a tendency (p = 0.06) for an interaction in CATHL5 mRNA expression, with the RES + OCM group showing greater expression compared to the CON + OCM (p = 0.07) and RES − OCM (p = 0.08) groups.DiscussionOur findings suggest that while restricted maternal nutrition did not affect mRNA expression of AMP, OCM supplementation modulated AMP expression in both fetal and maternal tissues. Further research is needed to elucidate the mechanisms underlying OCM’s impact on AMP expression.